Letter (copy) : Trade Union foodship for Spain - Citrine, Walter, 1887-1983
030-0050-001 International. AEC/AT/392 19th September, 1938. Mr. W. Elger, General Secretary, Scottish T.U.C., 33 Elmbank Crescent, Glasgow, C.3. Dear Mr Elger TRADE UNION FOODSHIP FOR SPAIN We have now learned from the International Federation of Trade Unions that the following is the mark for your shipment to Valencia: Jose Castre, Fondo Internacional de Solidaridad, Bonrepos, Valencia. Yours faithfully, General Secretary. 292/946/30/50